Cranial base angulation and linear dimensions in Class I, II and III sagittal jaw relationships in a Nigerian population: A cephalometric study - Aghimien OA; Ize-Iyamu IN (Ibom Medical Journal)
Background: Controversies still exist on the role of cranial base in the classification of jaw discrepancies. This present study was conducted to determine the role of cranial base in the classification of jaw discrepancies among a Nigerian population.